Short-term and long-term impacts of eco-driving on dynamics of driving behaviour and operating parameters - Savković, Tatjana; Miličić, Milica; Tanackov, Ilija; Pitka, Pavle; Koleška, Dejan (Transport, 2020)
This paper shows the impact of eco-driving training course on driving behaviour of 7 drivers, analysing two internal parameters: Scania Driver Support (SDS) parameter and Fuel Consumption (FC). Data were collected using Scania Fleet Management System (Scania FMS) over a period of one-year (1 + 2 + 4 + 6 months during the 2015 and 2016). Data for these two parameters of all drivers were recorded daily over a one-year period and calculated in average values on a monthly basis. A one-year cycle of average monthly ambient temperatures of wider geographical region was adopted as the most important external parameter of impact on eco-driving benefits. Longitudinal observation period is divided into: one month initial period of establishing the parameter values before the training (one month), short-term with eco-driving (two months), short-term without eco-driving (four months) and long-term (six months). Significantly higher values of SDS parameter (p < 0.05) and significant reduction of FC (p = 0.0310 < 0.05) were established with a higher average ambient temperature over a short-term period. A partial increase of SDS parameter value (p < 0.10) was established over a long-term period but the level of FC reversed to the values as before the training (p = 0.7554 > 0.05). The results indicate the potential of eco-driving training that manifests significantly positive effects only in good driving conditions. With bad weather conditions that correlate with bad driving conditions, the effects of eco-driving training are supressed with increased requirements for safer driving. Primary conclusion of the paper is that the eco-driving training principles have an apparent positive effect on reduction of FC and CO2 emission but are at the same time sensitive to environmental driving conditions.